2022
DOI: 10.3389/fphar.2022.993022
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring the pharmacological mechanisms of icaritin against nasopharyngeal carcinoma via network pharmacology and experimental validation

Abstract: Background: Icaritin is a natural product with a wide range of anti-tumor effects. However, its anti-tumor mechanism has not been thoroughly studied. This study examined the inhibitory effect of icaritin on nasopharyngeal cancer and its underlying mechanism using network pharmacology along with in vivo and in vitro experiments.Methods: MTT and clone formation assays were used to detect the effects of icaritin on the viability and proliferation of nasopharyngeal carcinoma cells, followed by the construction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The anticancer mechanisms of action of icaritin include inhibition of proliferation (Zhao et al, 2015) and ROS induction, (Liu et al, 2022) among others. Nevertheless, there is scarce information regarding clinical research on cancer therapy using icaritin (Table 4).…”
Section: Applications Of Icaritin In Cancer Therapy: Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer mechanisms of action of icaritin include inhibition of proliferation (Zhao et al, 2015) and ROS induction, (Liu et al, 2022) among others. Nevertheless, there is scarce information regarding clinical research on cancer therapy using icaritin (Table 4).…”
Section: Applications Of Icaritin In Cancer Therapy: Clinical Studiesmentioning
confidence: 99%
“…In nasopharyngeal carcinoma cell lines, icaritin showed good antitumor activity (inhibiting viability and proliferation and inducing S‐phase arrest). Moreover, the apoptotic activity induction was not significant, suggesting that this antitumor property is not a viable mechanism of icaritin for this cancer type (Liu et al, 2022).…”
Section: Preclinical Anticancer Studiesmentioning
confidence: 99%
“…A CCK8 assay was used to detect cell proliferation. Cells were seeded in 96-well plates at a density of 5 × 10 3 cells per well, and after 24 h, different concentrations of icaritin (5,10,20,40,60,80, and 100 μM) were added to the cells, which were cultured for 24, 48, or 72 h. Then, 10 μL of CCK8 solution was added to the cultures, which were further incubated at 37°C for 2 h. The absorbance was measured at 450 nm using a standard instrument. Each group was tested in triplicate.…”
Section: Cck8 Assaymentioning
confidence: 99%
“…Icaritin is the hydrolytic form of icariin, which may be isolated from plants of the genus Epimedium; this compound exerts an anti-tumor effect in a variety of tumor types including lung cancer [3], breast cancer [4], prostate cancer [5], acute myeloid leukemia, and liver cancer [6,7]. The anti-tumor mechanism of icaritin primarily involves promoting tumor cell apoptosis and necrosis [8,9], inducing cell cycle arrest [10], inhibiting tumor angiogenesis [11,12], and interfering with tumorrelated signaling pathways, such as the MAPK/ERK/JNK and PTEN/Akt/HIF-1α pathways [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Icaritin has good anti‐tumor effects both in vivo and in vitro. Studies have shown that icaritin can inhibit the proliferation of NPC cells by promoting ROS production, damaging DNA, and inducing S‐phase arrest, and its mechanism is related to the regulation of p53/p21 signaling pathway (Liu, Hu, et al., 2022).…”
Section: Natural Products That Target Nasopharyngeal Carcinomamentioning
confidence: 99%